2015
DOI: 10.1002/jid.3133
|View full text |Cite
|
Sign up to set email alerts
|

Does Training Really Matter to the Rural Poor Borrowers in Bangladesh? A Case Study on BRAC

Abstract: The goal of this study was to assess the effect of training programme on the healthcare expenses of the households under BRAC's microcredit programme. This study showed that training played a significant role in improving the healthcare expenditure of the household. Other socioeconomic variables such as household income, family size, age of the borrower, noninstitutional loan received by borrowers, amount of microcredit received from BRAC by borrowers, amount of loan instalment and distance of rural market fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
(28 reference statements)
0
8
0
3
Order By: Relevance
“…Rural women's economic activities are mainly confined to the household chores, and their mobility outside the home is also much restricted because of the existing patriarchal norms (Hilton et al, 2016;Kabeer, 2001;Mahmud et al, 2014;Murshid & Ball, 2018).The number of occupations is also limited to the rural women (Kabeer, 2001;Mahmud et al, 2014). Rural women have a lack of ownership and control over property such as land (Khan, et al, 2016;Uddin et al, 2016).…”
Section: Status Of Rural Women In Bangladeshmentioning
confidence: 99%
“…Rural women's economic activities are mainly confined to the household chores, and their mobility outside the home is also much restricted because of the existing patriarchal norms (Hilton et al, 2016;Kabeer, 2001;Mahmud et al, 2014;Murshid & Ball, 2018).The number of occupations is also limited to the rural women (Kabeer, 2001;Mahmud et al, 2014). Rural women have a lack of ownership and control over property such as land (Khan, et al, 2016;Uddin et al, 2016).…”
Section: Status Of Rural Women In Bangladeshmentioning
confidence: 99%
“…Training is closely related to the living-standard of a person which assists in increasing skills, production, income and management capacity (Hilton et al ., 2016; Mahmud et al ., 2014a; Mahmud et al ., 2017). In Bangladesh, several studies had been conducted to assess the role of training programs focusing on various socioeconomic issues relating to standard of living.…”
Section: Previous Studies On the Role Of Training Programs On Standard Of Livingmentioning
confidence: 99%
“…In Bangladesh, several studies had been conducted to assess the role of training programs focusing on various socioeconomic issues relating to standard of living. As for example, Hilton et al . (2016) found that the household health-care expenditure of rural poor women borrowers of BRAC (a reputable NGO) was increased because of the intervention of BRAC’s training program.…”
Section: Previous Studies On the Role Of Training Programs On Standard Of Livingmentioning
confidence: 99%
See 2 more Smart Citations